Experience with Nuclear Medicine Information System - Volkan-Salanci, Bilge (Galenos Publishing, 2012)
Objective: Radiology information system (RIS) is basically evolved for the need of radiologists and ignores the vital steps needed for a proper work flow of Nuclear Medicine Department. Moreover, CT/MRI oriented classical PACS systems are far from satisfying Nuclear Physicians like storing dynamic data for reprocessing and quantitative analysis of colored images. Our purpose was to develop a workflow based Nuclear Medicine Information System (NMIS) that fulfills the needs of Nuclear Medicine Department and its integration to hospital PACS system. Material and Methods: Workflow in NMIS uses HL7 (health level seven) and steps include, patient scheduling and retrieving information from HIS (hospital information system), radiopharmacy, acquisition, digital reporting and approval of the reports using Nuclear Medicine specific diagnostic codes. Images and dynamic data from cameras of are sent to and retrieved from PACS system (Corttex©) for reprocessing and quantitative analysis. Results: NMIS has additional functions to the RIS such as radiopharmaceutical management program which includes stock recording of both radioactive and non-radioactive substances, calculation of the radiopharmaceutical dose for individual patient according to body weight and maximum permissible activity, and calculation of radioactivity left per unit volume for each radionuclide according their half lives. Patient scheduling and gamma camera patient work list settings were arranged according to specific Nuclear Medicine procedures. Nuclear Medicine images and reports can be retrieved and viewed from HIS. Conclusion: NMIS provides functionality to standard RIS and PACS system according to the needs of Nuclear Medicine. Conflict of interest:None declared.